Pixuna virus modifies host cell cytoskeleton to secure infection - Gil, Pedro Ignacio (2017)
Pixuna virus (PIXV) is an enzootic member of the Venezuelan Equine Encephalitis Virus complex and belongs to the New World cluster of alphaviruses. Herein we explore the role of the cellular cytoskeleton during PIXV replication. We first identified that PIXV undergoes an eclipse phase consisting of 4 h followed by 20 h of an exponential phase in Vero cells. The infected cells showed morphological changes due to structural modifications in actin microfilaments (MFs) and microtubules (MTs). Cytoskeletonbinding agents, that alter the architecture and dynamics of MFs and MTs, were used to study the role of cytoskeleton on PIXV replication. The virus production was significantly affected (p < 0.05) after treatment with paclitaxel or nocodazole due to changes in the MTs network. Interestingly, disassembly of MFs with cytochalasin D, at early stage of PIXV replication cycle, significantly increased the virus yields in the extracellular medium (p < 0.005). Furthermore, the stabilization of actin network with jasplakinolide had no effect on virus yields. Our results demonstrate that PIXV relies not only on intact MTs for the efficient production of virus, but also on a dynamic actin network during the early steps of viral replication.